Morphometric Analysis and Genetic Relationship of Rasbora spp. in Sarawak, Malaysia - Aimi Wahidah Aminan; Leonard Lim Whye Kit; Chung Hung Hui; Badiozaman Sulaiman (Tropical Life Sciences Research, 2020)
The genus Rasbora is one of the most species-rich genus among the freshwater fishes and cryptic diversity has been a major hindrance in species identification in the past four decades due to their high similarities in terms of morphology. This study aimed to investigate this issue both morphologically and molecularly. In this study, a total of 23 morphometric parameters were used to differentiate the 103 Rasbora fish samples harvested from different regions of Sarawak state of Malaysia via Multivariate Stepwise Discriminant Function Analysis (SDFA). Then, cytochrome oxidase subunit I (COI) gene was utilised to further distinguish 33 of these fishes, followed by sequence and phylogenetic analysis. Our results unravelled pre-anal length as strongest morphometric discriminant (100%) and that all eight Rasbora species tested are monophyletic except for R. sumatrana and R. caudimaculata, revealing possible cryptic Rasbora species. Further investigations are vital to enrich the data from this study for Rasbora cryptic diversity and conservation studies in future. Genus Rasbora adalah salah satu daripada genus yang memiliki kerencaman spesies yang paling tinggi dalam kalangan ikan air tawar dan kepelbagaian krip telah menjadi penghalang utama dalam pengecaman spesies sepanjang empat dekad disebabkan persamaannya yang tinggi dari segi morfologi. Kajian ini bertujuan untuk mengkaji isu-isu morfologi dan molekular. Dalam kajian ini, 23 parameter morfometrik telah digunakan untuk membezakan 103 sampel ikan Rasbora yang dikutip daripada daerah berbeza di negeri Sarawak, Malaysia menggunakan Multivariate Stepwise Discriminant Function Analysis (SDFA). Kemudian, gen cytochrome oxidase subunit I (COI) digunakan untuk membezakan 33 jenis ikan ini, diikuti dengan analisis jujukan dan analisis filogenetik. Keputusan menunjukkan panjang pra-anal sebagai morfometrik diskriminan terkuat (100%) dan kesemua lapan spesies Rasbora yang diuji adalah monofiletik kecuali R. sumatrana and R. caudimaculata, dan mendedahkan spesies Rasbora yang mungkin krip. Penyelidikan lebih lanjut adalah sangat penting untuk memperkayakan data dari kajian ini untuk kepelbagaian dan pemuliharaan krip di masa akan datang.